2019
DOI: 10.51758/agjsr-03-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing value-based financing for achieving SDGs: Social innovation model for Arab municipalities

Abstract: It is inconceivable to achieve Sustainable Development Goals (SDGs) at the national level without accomplishing them locally. In the Arab region, municipalities face challenges to meet a widening gap between expenses and revenues. Securing a locally based sustainable financing model is of paramount importance. Wāqf is a value-based funding model that can offer new opportunities for sustainable financing to achieve SDGs locally. It agrees with Islamic law with the intent to promote social cohesion. The paper ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As research by Kasri & Ismail (2021) also explains sustainable business analysis including governance, transparency, and social impact created, which can add value to the waqf sector globally as part of seeking sustainable and feasible contemporary alternatives to the waqf model. This is done due to optimizing the use of waqf for sustainable finance This indicates that driving sustainable Islamic finance not only in terms of finance in banking but can be done by optimizing Islamic social financial instruments, such as waqf which in this literature has been discussed quite a lot (Abduh, 2019;Abdullah, 2014;Adnan et al, 2021, Alshaleel, 2019Aslam & Bhatti, 2021;Hassana et al, 2020;Iskandar et al, 2021;Kasim et al, 2016;Budalamah et al, 2019;Noor et al, 2016;Rosman et al, 2019;Sulaiman et al, 2019;Tajudin et al, 2020;Umar & Danlami, 2022;Zain et al, 2019;Zain & Sori, 2020) .…”
Section: Resultsmentioning
confidence: 99%
“…As research by Kasri & Ismail (2021) also explains sustainable business analysis including governance, transparency, and social impact created, which can add value to the waqf sector globally as part of seeking sustainable and feasible contemporary alternatives to the waqf model. This is done due to optimizing the use of waqf for sustainable finance This indicates that driving sustainable Islamic finance not only in terms of finance in banking but can be done by optimizing Islamic social financial instruments, such as waqf which in this literature has been discussed quite a lot (Abduh, 2019;Abdullah, 2014;Adnan et al, 2021, Alshaleel, 2019Aslam & Bhatti, 2021;Hassana et al, 2020;Iskandar et al, 2021;Kasim et al, 2016;Budalamah et al, 2019;Noor et al, 2016;Rosman et al, 2019;Sulaiman et al, 2019;Tajudin et al, 2020;Umar & Danlami, 2022;Zain et al, 2019;Zain & Sori, 2020) .…”
Section: Resultsmentioning
confidence: 99%
“…Localizing the SDGs enables nations to attain SDG-specific targets (Budalamah et al, 2019). Target 15.8.…”
Section: Discussionmentioning
confidence: 99%
“…Since metropolitan areas are the engine of economic development, the locale of human injustice and the cause of environmental evils, SDG 11 largely links SDGs 1 to 15. Budalamah et al (2019) investigated the linkages between the 17 SDGs. Their cluster analysis indicated that SDG 11 serves as an estuary for SDGs 1 to 15.…”
Section: Introductionmentioning
confidence: 99%